Spatial Identity of the Bolgarian Community in the Polyethnic Moldova - G. I. Ostapenko (Сравнительная политика, 2015)
Ethnopolitical processes in Moldova have provided for actualization of local ethnoses’ national identities. Ethnoses, which have formed own territorial community, have got a chance to become valid political actors on the nationwide level. Such status allows ethnoses to consider own future in context of geopolitical perspectives, produce own unique interpretations of space, where they are placed, or modify them depending on external conditions. This paper investigates Moldova’s Bulgarians’ spatial identity and ethnonational self-identification on the example Bulgarian territorial community, which is in a position of choice one of spatial interpretations.